Optimizing German Speaking Skills with Mentimeter Interactive Media - Syaputra, Arlian Fachrul; Angreany, Femmy; Mannahali, Misnah (Phonologie : Journal of Language and Literature, 2024)
Abstract. The purpose of this study was to investigate the effectiveness of Mentimer in learning German speaking. This study use quasiexperimental approach which involved a control group and an experiment group. Mentimeter media was implemented in the experiment group during 5 meetings. Students’ performance was measured before and after the implementation of learning process. Data were analyzed using descriptive statistics and inferential statistics. Descriptive statistics aimed to describe and categorize the levels of students’ performance, while inferential statistics aimed to discover whether there was a significant influence of mentimeter media in increasing students’ performance. Results show that the sig value of the experiment class is 0.00. It proves that Mentimeter media is effective in increasing students’ performance as the sig. value is lower than 0.05.  Keywords: Mentimeter, Web Based Learning Media Speaking, German, Learning Media